(untitled) (Journal of Economic Research & Business Administration, 2016)
The study of indirect taxation issues at the present stage is of particular importance, since taxes express the fiscal interests of the state. Judicious use can positively influence the process of pricing and affect consumption patterns. One of the main problems in the area of taxation is to achieve the optimal value of tax collection. Taxes are the primary vehicle through which the image of the state and local money funds. For any state, at whatever stage of their economic and social development, it may be, the need to increase budget revenues is one of the most urgent tasks. Finding the right solution to this problem is extremely important for Kazakhstan economy. Factors adversely affecting the collection of indirect taxes include: a decline in production, the heavy financial and economic position of enterprises, the growth of non-payment companies, the provision of a large number of exemptions and deferrals, the introduction of “zones of economic preference” tax evasion. After analyzing After analyzing revenues of indirect taxes in the state budget revenues shows that in the structure of tax payments the share of indirect taxes decreased year by year, in 2013 the proportion was 30.0%, in 2014 – 26.6%, in 2015 – 22 , 7%, and the data shows the timeliness of the changes in tax legislation.